The Role of CT Perfusion in Predicting the Neuropsychological Outcome of Patients with Mild and Moderate Traumatic Brain Injury - Singla, Kunal; Dev, Rahul; Rawat, Vikarm Singh; Arora, Rajnish Kumar; Sadhasivam, Saravanan (Indian Journal of Neurotrauma, 2025)
Objective Patients with traumatic brain injury (TBI) often continue to have symptoms of neuropsychological dysfunction. Studies have demonstrated cerebral perfusion (CP) deficits following TBI. There is limited literature on the association between CP and neuropsychological outcomes following TBI. This study aimed to analyze the correlation between neuropsychological outcome and CP in patients with mild to moderate TBI.Materials and Methods Patients with mild to moderate TBI and computed tomography (CT) scan suggestive of diffuse axonal injury underwent CT perfusion scan within 48 hours of injury. All patients were evaluated with various neuropsychological tests at 3 months of follow-up. The correlation between CP and neuropsychological outcome was assessed.Results Forty patients (21 with TBI mild and 19 with moderate TBI) were enrolled. Among 21 patients with mild head injury, 14 (66.7%) showed evidence of hypoperfusion in the right frontal lobe and 12 (57.1%) in the right parietal lobe. Among 19 patients with moderate head injury, 12 (63.1%) patients showed hypoperfusion in the right frontal lobe and 7 (36.8%) in the right parietal lobe. CP in the bilateral frontal and left temporal lobe white matters showed a statistically significant negative correlation with the number of mistakes committed in the Stroop A, B, and C tests. Perfusion in the left temporal white matter showed a negative correlation with the trail making test (parts A and B) and a positive correlation with the animal fluency test. The right parietal and left frontal lobes also showed a positive correlation with the AFT.Conclusion We found a significant correlation between CP of the white matter of different lobes during the acute phase of TBI and neuropsychological performance at 3 months after TBI.
Keywords: cerebral perfusion; CT perfusion; mild head injury; moderate head injury; neuropsychological outcome; traumatic brain injury